Improved detection capabilities of molecular emission in microwave-enhanced laser-induced plasma - García-Gómez, Laura; Soriano, J.K.; Vadillo-Pérez, José Miguel; Ikeda, Y. (Elsevier, 2026)
The detection of molecular emissions in laser-induced breakdown spectroscopy (LIBS) remains a subject of active research, driven by the need to improve both signal-to-noise ratios and spectral definition. Various enhancement strategies have been proposed, including double-pulse configurations and hybrid systems combining LIBS with complementary techniques like Raman spectroscopy or laser-induced fluorescence. While effective, these methods often introduce considerable experimental complexity. In this context, the present study explores microwave re-excitation (MW-LIBS) as a more accessible alternative capable of modifying plasma dynamics without additional optical alignment. The introduction of microwave energy increases collisional activity within the plasma, extending its duration to the millisecond range and amplifying emission signals. Molecular species were monitored under this regime, focusing on canonical emitters such as CN and CaO, as well as less commonly reported systems like SnO, which has not been previously described in LIBS literature. The most significant enhancements were observed under conditions approaching the plasma ablation threshold. Moreover, MW-LIBS enabled the observation of molecular emissions in the red and near-infrared regions, which are generally limited in conventional LIBS due to detector inefficiencies and reduced plasma radiative output. These findings provide new insights into the mechanisms of molecular formation in sustained plasmas and demonstrate the potential of MW-LIBS for enhancing molecular diagnostics.
Disponible online desde octubre 2025
Keywords: Espectroscopía de plasma inducido por láser; Láseres en física; Química analítica; LIBS; MW-LIBS; Re-excitation; Molecular emission